Freqüência de pneumonite em adultos subnutridos autopsiados. - Jammal, Millena Prata (2009)
Background: Chronic protein-energy malnutrition (PEM) can affect structure and function of the lungs, and therefore our aim was to verify the hypothesis that autopsied malnourished adults would have higher pneumonia frequency than non-malnourished ones, and to compare the percentage of pneumonia between cases with or without acute phase response (APR) a condition often associated with protein malnutrition. Methods: All adults (age> 18y) autopsied at the School Hospital of the Triangulo Mineiro Federal University, Uberaba, Brazil, between 1994 and 2007 were included. Body weight, height, body mass index (kg/m2) were included, in addition to autopsy findings and macro and microscopy pneumonia diagnosis. PEM was assessed by BMI less than 18.5kg/m2, and APR was defined by 1) death secondary to severe infection plus one of the following criterion 2) acute gastric stress ulcers or 3) spleen reactive state or 4) fat liver. Groups were compared by t , Wilcoxon Mann-Whitney, and chi-square tests, a p less than 0.05 was considered significant. Results: Overall pneumonia was observed among 87.6% of the 213 studied cases. Malnourished (n=63) and non-malnourished (n=150) groups had, respectively, similar frequency of pneumonia at macro (60.3 vs. 58.7%) and microscopy (90.5 vs. 84.7%). Pneumonia percentage was higher among APR-positive group than APR-negative ones, at macro (84 vs. 34.6%) and microscopy (93.4 vs. 79.4%). Lung histology revealed that pneumonia was predominantly diffuse, with mild or moderate mononuclear infiltrates within alveoli or septa in great extension also associated with interstitial or alveolar edema. Conclusions: Pneumonia was observed in high percentage (87.6%) of adults autopsied at the School Hospital of the Triangulo Mineiro Federal University. Our data do not support the hypothesis that chronic malnourished adults have higher pneumonia frequency than non-malnourished ones. However, cases with increased risk of protein malnutrition the APR-positive ones showed higher pneumonia frequency than APR-negative ones.